The discourse of the narrative character in Maha Hassan’s novels - Sara Zaid Mahmood; Latif Muhammad Hasan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This paper, entitled (The Discourse of the Narrative Character in Maha Hassan’s Novels), deals with the awareness of the fictional characters themselves and the problems of the reality in which they live. It aims at shedding light on the discourse mechanism of the narrative character in the novels of "Maha Hassan". In this context, the paper reveals the fictional characters’s vision of the world. Moreover, it explores their manners, actions, behaviors, and awareness of the facts surrounding them. The researcher chose two types of characterization in Maha Hassan’s narrative discourse, namely: the round character and the flat character, which the novelist took special care of in comparison to the other types. She applied the (formative structuralism) approach, which is appropriate to show the real value of the literary work, and to show the relationship between the artistic structure on the one hand, and the objective structure on the other hand, as well as the social and historical structure. The fictional work - especially the novels of Maha Hassan - cannot be independent of society and its transformations, as they are novels that include autobiographical impressions, real events and narrative fantasies. In conclusion, the research arrived at several results, the most important of which are: The discourse of the woman characters in the novels of "Maha Hassan" appears strong and dominant.